2022
DOI: 10.5194/nhess-22-2117-2022
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of meteorological conditions for rockfall triggers in Germany

Abstract: Abstract. A rockfall dataset for Germany is analysed with the objective of identifying the meteorological and hydrological (pre-)conditions that change the probability for such events in central Europe. The factors investigated in the analysis are precipitation amount and intensity, freeze–thaw cycles, and subsurface moisture. As there is no suitable observational dataset for all relevant subsurface moisture types (e.g. water in rock pores and cleft water) available, simulated soil moisture and a proxy for por… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 44 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…We analysed an area notedly larger than Germany, which illustrates that similar changes in the meteorological conditions affect the entire study area. In a previous study we have shown that precipitation is the most effective triggering factor for rockfall in the German lower 245 mountain ranges (Nissen et al, 2022). Even though heavy precipitation is predicted to increase as a consequence of global warming (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…We analysed an area notedly larger than Germany, which illustrates that similar changes in the meteorological conditions affect the entire study area. In a previous study we have shown that precipitation is the most effective triggering factor for rockfall in the German lower 245 mountain ranges (Nissen et al, 2022). Even though heavy precipitation is predicted to increase as a consequence of global warming (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, a decrease in rock fall probability needs to be considered due to a potentially balancing effect of increased evapotranspiration from increased temperatures as well as temperature driven changes in soil water regimes (Dehn and Buma, 1999;Collison et al, 2000). The statistical model applied in this study therefore considers the combined effect of precipitation, freeze-thaw cycles and fissure water (Nissen et al, 2022). The model was developed for rockfall occurrences in the German lower mountain ranges, a study region that does not include areas with permafrost.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations